Lyot-filter-based multiwavelength fiber laser using a semiconductor optical amplifier assisted by nonlinear polarization rotation effect - Sulaiman, Abdul Hadi (2015)
Research works based on multiwavelength fiber laser (MWFL) were realized by utilizing several types of comb filter such as Lyot filter, Mach-Zehnder interferometer and Sagnac loop mirror interferometer. The generation of MWFL based on Lyot filter is highly interesting to be explored due to its advantage of narrow linewidth, low power loss and simple structure. The multiwavelength generation based on Lyot filter has several issues that need to be focused such as narrow wavelength range and hardly explored of bidirectional configuration. This doctoral research focuses on both issues, where they are closely related to the research objective that is wavelength range improvement and a new design of bidirectional configuration within the Lyot filter scope. In this doctoral research, an ability of intensity equalizer is utilized to flatten the spectrum, and it is obtained from an effect of nonlinear polarization rotation (NPR) which is induced from a combination of semiconductor optical amplifier (SOA) and polarizer. This NPR effect induces two mechanisms of intensity dependent transmission (IDT) or intensity dependent loss (IDL), which depends on the adjustment of polarization controller (PC). To obtain a flat multiwavelength spectrum, the adjustment of the PC and the intensity is very important in order to achieve high cavity loss in the IDT and IDL mechanisms. The first main finding in this study is about a wide wavelength range of 30.7 nm based on a unidirectional Lyot filter. The best performance has 307 number of lines within 5 dB bandwidth. The channel spacing for the most data is 0.1 nm due to the length of polarization maintaining fiber of 53.2 m. The highest extinction ratio and peak power is 12 dB and -43 dBm, respectively. The flatness deteriorates with intensity increment due to the IDT mechanism in the cavity. Without the use of polarizer in the experimental structure, no multiwavelength spectrum is generated because the polarizer is an important component in inducing the IDT mechanism. The next main finding is a new design of bidirectional Lyot filter. This filter is unique because the incoming lights to the filter can propagate simultaneously in two different directions of clockwise and counter clockwise. This advanced filter can has two simultaneous constructive interferences, where it can give an advantage of light reshaping for a flat spectrum generation. The best multiwavelength performance based on this new filter produces 96 number of lines within 5 dB bandwidth, with high peak power of -34 dBm. This design can be simply changed to a unidirectional configuration, but the spectrum flatness is deteriorated because the occurrence of constructive interference is only once. The multiwavelength performance is also deteriorated when the laser structure is modified into different coupling ratio of optical coupler, different SOA type, configuration of bidirectional SOA and without polarizer in the laser structure. In conclusion, this doctoral research has successfully solved the issues of multiwavelength performance based on Lyot filter. The wavelength range is wider as compared to the previous works, while a new structure of bidirectional Lyot filter is successfully designed.